REVITALISASI NILAI PANCASILA SEBAGAI PONDASI IDENTITAS NASIONAL DI TENGAH PENGARUH GLOBALISASI STUDI KASUS DESA KENANGAN BARU - Anni Latifah; Sabrina Umami Pane; Tamara Sesi Sihaloho; Angel Tio Lina Aritonang; Nazwa Refany; Parlaungan Gabriel Siahaan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the influence of globalization on the internalization of Pancasila values and to examine strategies for revitalizing these values as the foundation of national identity in Kenangan Baru Village, Percut Sei Tuan District, Deli Serdang Regency. Globalization brings various changes to people's social lives, especially in their mindset, lifestyle, and social interactions, which can potentially affect their understanding and practice of national values. This study uses a qualitative approach with a descriptive method. Data was obtained through observation, interviews, and documentation of community leaders, village officials, and local residents. The results of the study show that globalization has influenced changes in communication patterns, lifestyles, and people's views on national values. However, the people of Kenangan Baru Village still strive to maintain Pancasila values through social activities such as mutual cooperation, deliberation, and religious activities. The revitalization of Pancasila values can be achieved through strengthening Pancasila education, enhancing the role of community and religious leaders, and utilizing information technology and social media as educational tools for the younger generation. These efforts are expected to strengthen the understanding and practice of Pancasila values as the basis for maintaining national identity amid the tide of globalization.